CSF levels of Chitinase3like1 correlate with early response to cladribine in multiple sclerosis - Marastoni, Damiano; Foschi, Matteo; Eccher, Chiara; Crescenzo, Francesco; Mazziotti, Valentina; Tamanti, Agnese; Bajrami, Albulena; Camera, Valentina; Ziccardi, Stefano; Guandalini, Maddalena; Bosello, Francesca; Anni, Daniela; et al. (Frontiers in Immunology, 2024)
Background. Cladribine has been introduced as a high-efficacy drug for treating relapsing-remitting multiple sclerosis (RRMS). Initial cohort studies showed early disease activity in the first year after drug initiation. Biomarkers that can predict early disease activity are needed. Aim. To estimate cerebrospinal fluid (CSF) markers of clinical and radiological responses after initiation of cladribine. Methods. Forty-two RRMS patients (30F/12M) treated with cladribine were included in a longitudinal prospective study. All patients underwent a CSF examination at treatment initiation, clinical follow-up including Expanded Disability Status Scale (EDSS) assessment, and a 3T MRI scan after 6,12 and 24 months, including the evaluation of white matter (WM) and cortical lesions (CLs). CSF levels of 67 inflammatory markers were assessed with immune-assay multiplex techniques. The 'no evidence of disease activity' (NEDA-3) status was assessed after two years and defined by no relapses, no disability worsening measured by EDSS and no MRI activity, including CLs. Results. Three patients were lost at follow-up. At the end of follow-up, 19 (48%) patients remained free from disease activity. IFNgamma, Chitinase3like1, IL32, Osteopontin, IL12(p40), IL34, IL28A, sTNFR2, IL20 and CCL2 showed the best association with disease activity. When added in a multivariate regression model including age, sex, and baseline EDSS, Chitinase 3 like1 (p = 0.049) significantly increased in those patients with disease activity. Finally, ROC analysis with Chitinase3like1 added to a model with EDSS, sex, age previous relapses, WM lesion number, CLs, number of Gad enhancing lesions and spinal cord lesions provided an AUC of 0.76 (95%CI 0.60-0.91). Conclusions. CSF Chitinase 3 like1 might provide prognostic information for predicting disease activity in the first years after initiation of cladribine. The drug's effect on chronic macrophage and microglia activation deserves further evaluation.